2019
DOI: 10.1002/phar.2261
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐Dose Four‐Factor Prothrombin Complex Concentrate for Vitamin K Antagonist Reversal: Does One Dose Fit All?

Abstract: Four-factor prothrombin complex concentrate (4F-PCC) has emerged as the preferred option for emergent reversal of vitamin K antagonists (VKAs); however, the optimal dosing strategy is unknown.Although several studies have attempted to determine the optimal dose of 4F-PCC using a variety of dosing regimens, no dosing strategy has been found to be superior. Many of these studies have evaluated a low, fixed dose of 4F-PCC rather than individualized dosing as recommended in product labeling. The purpose of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Even before United States Food and Drugs Administration approval, no dose-finding studies had been performed and dosing recommendations in national guidelines vary largely. Authors of recent systematic reviews could not perform a meta-analysis due to heterogeneity [22,23].…”
Section: Vitamin K Antagonist Reversalmentioning
confidence: 99%
“…Even before United States Food and Drugs Administration approval, no dose-finding studies had been performed and dosing recommendations in national guidelines vary largely. Authors of recent systematic reviews could not perform a meta-analysis due to heterogeneity [22,23].…”
Section: Vitamin K Antagonist Reversalmentioning
confidence: 99%
“…Other studies have also demonstrated the efficacy of fixed, weight-based dosing of 4F-PCC for INR reversal [11][12][13]. Mohrien et al used a fixed, weight-based (30 IU/kg) dosing protocol of 3-factor PCC (3F-PCC) which demonstrated 85.7% reversal of INR to target without significant adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…However, higher doses may be needed to treat ICH or a higher baseline INR. 75 Nevertheless, in the absence of an ideal dose suitable for all, variable dosing per label instructions is preferred by many institutions.…”
Section: Discussionmentioning
confidence: 99%